2017
DOI: 10.1523/jneurosci.1660-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intraneural Injection of ATP Stimulates Regeneration of Primary Sensory Axons in the Spinal Cord

Abstract: Injury to the peripheral axons of sensory neurons strongly enhances the regeneration of their central axons in the spinal cord. It remains unclear on what molecules that initiate such conditioning effect. Because ATP is released extracellularly by nerve and other tissue injury, we hypothesize that injection of ATP into a peripheral nerve might mimic the stimulatory effect of nerve injury on the regenerative state of the primary sensory neurons. We found that a single injection of 6 μl of 150 μm ATP into female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 52 publications
(61 reference statements)
0
11
0
1
Order By: Relevance
“…Axonal transport of mitochondria has been shown to boost regrowth in C. elegans and mammalian neurons [24][25][26]. Our observations suggest that more sustained [Ca 2+ ] mt uptake also promotes axon regrowth, for example potentially through increasing ATP production required for axon repair [61]. We speculate that the mild enhancement of [Ca 2+ ] mt uptake resulting from elevated MICU expression is insufficient to trigger deleterious consequences such as opening of the mitochondrial permeability transition pore that would lead to axonal degeneration.…”
Section: Discussionmentioning
confidence: 78%
“…Axonal transport of mitochondria has been shown to boost regrowth in C. elegans and mammalian neurons [24][25][26]. Our observations suggest that more sustained [Ca 2+ ] mt uptake also promotes axon regrowth, for example potentially through increasing ATP production required for axon repair [61]. We speculate that the mild enhancement of [Ca 2+ ] mt uptake resulting from elevated MICU expression is insufficient to trigger deleterious consequences such as opening of the mitochondrial permeability transition pore that would lead to axonal degeneration.…”
Section: Discussionmentioning
confidence: 78%
“…Meanwhile, spontaneous dendritic plasticity could reflect a compensatory response of the spinal cord to the functional deficits caused by the injury (45,46) As yet, one of the important strategies for treating SCC is to promote axon regeneration in the epicenter (49). Data demonstrated that decreased CPLX1 expression promoted axon regrowth even when neurons were incubated in an inhibitory environment through highly up-regulation of GAP43 involving in axonal growth and regeneration (25,50). We then investigated whether GV treatment promotes regrowth of descending axons in vivo, which mediate voluntary motor movement, important for locomotion (10).…”
Section: Discussionmentioning
confidence: 99%
“…En el presente estudio un volumen 100 µL fue suficiente para ocasionar un aumento considerable del volumen intraneural en el sitio de lesión evitando generar un daño adicional. Este volumen se asemeja al elegido por Wu et al (2018) en donde se expuso al nervio a inyecciones intraneurales de 6 µl a 150 µL de ATP.…”
Section: Discussionunclassified